PENGAJARAN HASIL KALI TITIK DAN HASIL KALI SILANG PADA VEKTOR SERTA BEBERAPA PENGEMBANGANNYA - -, Suwandi (Edu Research, 2015)
Dot product and cross product can be interperetation by geometry so easyunderstand about dot product and cross product. In this paper discuss, interpretation dot product and cross product by geometry and proof formula cosinus sum angel and minus by dot product, and connect dot product and cross product with determinant.